The Principle of “equal economic participation” and methods of allocation of surplus in cooperative associations, case studies for the area of construction (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
This research was aimed to analyze the general principle of "Equal Economic Participation" to see the practical application of the methods of distribution of surplus in the cooperative associations, through case studies for the construction area. To achieve these objectives it is fundamental a qualitative approach, with a descriptive type and documentary design. Three cooperatives were established as units of analysis, located in the west area of Iribarren County of the city of Barquisimeto, Lara State, intentionally selected, as a collection technique, open and comprehensive answers were applied that allowed to obtain information from the main actors/protagonists of cooperative associations. The analyses of the results are organized according to data on the instrument to collect data. Finally conclusions and recommendation were presented to be considered by members of cooperative associations in the implementation of this principle
Keywords: principle; cooperative; methods of distribution